ANALYSIS OF THE IMPLEMENTATION OF BOS FUNDS POLICY AT MTS IZHARUL HAQ GARUT FROM THE PERSPECTIVE OF ISLAMIC EDUCATION GOVERNANCE - Nenden Haprilwanti; Wina Sapitri; Supiana Supiana; Ara Hidayat (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
The School Operational Assistance (BOS) policy is a strategic government instrument to ensure the sustainability of educational services and to improve the quality of learning, including in madrasahs. However, in practice, the implementation of the BOS policy still faces various administrative and structural challenges, particularly in private educational institutions. This study aims to analyze the implementation of the BOS fund policy at MTs Izharul Haq Garut and to identify factors affecting its effectiveness from the perspective of Islamic education governance. This research employs a descriptive qualitative approach using a literature study enriched with empirical field data. The analysis is conducted using public policy implementation theories proposed by Edwards III, Grindle, and Mazmanian & Sabatier, as well as the good governance framework in Islamic education. The findings indicate that the implementation of the BOS policy at MTs Izharul Haq Garut has adhered to the principles of transparency and participation; however, it has not been optimal due to frequent regulatory changes, limited human resource capacity, and weak policy communication. Islamic values such as amanah (trustworthiness), justice, and accountability in educational management serve as important foundations for maintaining the integrity of BOS fund management. This study recommends the need for policy stability, strengthening digital administrative capacity in madrasahs, and the establishment of participatory policy feedback mechanisms.